Analisis Proses Penyelenggaraan Event: Studi Kasus Penyelenggaran “Grand Launching Mal Pelayanan Publik Kabupaten Gresik” oleh CV. Imagine Promosindo - Nugroho, Margaretta Andini; Meilia, Melania (University of Jember, 2022)
One of the success factors in organizing an event or activity lies in the careful and considerate preparation process. This is the full responsibility of the event organizer as the party given the authority to organize the entire series of events. CV. Imagine Promosindo is one of the leading event organizers in Malang Regency with more than 10 years of experience in handling events, both at local and national levels. The event